Low-bias negative differential resistance in junction of a benzene between zigzag-edged phosphorene nanoribbons. (6th June 2018) - Jia, Chunxia; Cao, Liemao; Zhou, Xiaoying; Zhou, Benliang; Zhou, Guanghui
Abstract: We study the electron transport properties through the junction of a benzene molecule in conjunction with two monolayer zigzag-edged phosphorene nanoribbon (ZPNR) electrodes by applying the nonequilibrium Green's functions in combination with the density functional theory. We find that the molecular junction with two phosphorus-carbon bonds exhibits an interesting low-bias negative differential resistance effect with a peak-to-valley ratio of 29, which originates from the edge states in ZPNR due to the anisotropic band structure of phosphorene. Importantly, the performance of the junction can be tuned via the molecule-ZPNR interface bonding. The findings may be useful in sensitive-device applications. Furthermore, the physical mechanisms are revealed and discussed in terms of the electronic transmission spectrum, the evolution of the frontier molecular orbitals, the local device density of states around the Fermi level, and the projected density of states.